Genetically Modified Mouse Models Used for Studying the Role of the AT2 Receptor in Cardiac Hypertrophy and Heart Failure - Maria D. Avila (Journal of Biomedicine and Biotechnology, 2011)
The actions of Angiotensin II have been implicated in many cardiovascular conditions. It is widely accepted that the cardiovascular effects of Angiotensin II are mediated by different subtypes of receptors: AT1 and AT2. These membrane-bound receptors share a part of their nucleic acid but seem to have different distribution and pathophysiological actions. AT1 mediates most of the Angiotensin II actions since it is ubiquitously expressed in the cardiovascular system of the normal adult. Moreover AT2 is highly expressed in the developing fetus but its expression in the cardiovascular system is low and declines after birth. However the expression of AT2 appears to be modulated by pathological states such as hypertension, myocardial infarction or any pathology associated to tissue remodeling or inflammation. The specific role of this receptor is still unclear and different studies involving in vivo and in vitro experiments have shown conflicting data. It is essential to clarify the role of the AT2 receptor in the different pathological states as it is a potential site for an effective therapeutic regimen that targets the Angiotensin II system. We will review the different genetically modified mouse models used to study the AT2 receptor and its association with cardiac hypertrophy and heart failure.